Przeciwko nostalgii… Koncepcja pamięci we wspomnieniach Fiodora Stiepuna „Бывшее и несбывшееся” - Ziomek, Marcin (Studia Rossica Posnaniensia, 2019)
The article offers an introduction into Fyodor Stepun’s culture-making concept of memory. The thinker – one of the most intriguing representatives of the Russian emigration – criticized the emigrant milieu for its excessive traditionalism. Stepun presented the force of memory as a counterbalance to reminiscence and nostalgia, claiming that memory can prevent the Russian cultural heritage from being forgotten and ensure that it will creatively form the future of reborn Russia.